HUBUNGAN TEKSTUR SEDIMEN DENGAN KEMELIMPAHAN LARVA POLYCENTROPODIDAE (TRICHOPTERA) DI WADUK SERMO, KULONPROGO, YOGYAKARTA - Jati, Wibowo Nugroho (Universitas Atma Jaya Yogyakarta, 2004)
A study on sediment texture to the abundance of Polycentropodidae?s larvae has been done in Sermo Water Reservoir, Kulonprogo, Yogyakarta. Samples have been taken in 3 rivers i.e. Ngrancah, Tegalrejo and Sidowayah. Four different depth were assessed i.e. 0 ? 5 m, 5 ? 10 m, 10 ? 15m, and 15 ? 20 m. Result showed that the larvae?s abaundance was hishest in Ngrancah river on depth of 0 ? 5 m with 53 ind/m2 and lowest on Tegalrejo river on depth of 15 ? 20 m with 3 ind/m2. The larvae?s abundance in every depth was characterized by sand texture and its depth.